PERKAWINAN DIBAWAH UMUR MENURUT HUKUM POSITIF DI INDONESIA (STUDI KASUS DI KECAMATAN TAMANSARI) - himmah, fiina; Gunadi (Ahwaluna | Jurnal Hukum Keluarga Islam, 2025)
Underage marriage is a marriage between a man and a woman who have not reached the minimum age of 19, as stipulated in Indonesian law. Generally, the couple is not yet physically, mentally, and emotionally mature. This phenomenon remains widespread in Indonesia and has various negative impacts. This study aims to identify the factors causing underage marriage in Tamansari District and its impacts. The method used is descriptive qualitative with normative, legal, and sociological approaches, through interviews, literature review, and documentation. The results indicate that the main causes of early marriage include: the child's own wishes, low education, economic factors, environmental factors, and promiscuity. Negative impacts include psychological disorders, early divorce, and economic problems. Keywords: Underage Marriage, Positive Law, Causal Factors